MORPHOLOGICAL CHANGES IN THE INTERSTITIAL TISSUE AND BLOOD VESSELS OF ZONA FASCICULATA IN CORTEX OF THE ADRENAL GLAND IN COVID-19 INFECTION (Conferencea, 2024)
In COVID-19 infection, severe dyscirculation, edema, hemorrhages and inflammatory infiltrates are observed in the interstitial tissue and blood vessels of the cortical layer of the adrenal gland. It is determined that the histotopographic area where the blood vessels are located, that is, the interstitial tissue, is subject to severe edema and hydration, especially in the subcapsular area, the interstitial tissue of zona glomerulosa and fasciculata, the edematous process is rapidly developing.